Pengaruh Transaksi Online Terhadap Minat Penggunaan Fintech dengan Model E-Money Layanan Shopeepay (Studi pada Generasi Z yang Berdomisili di Kecamatan Kemlagi) - Arindi Listasari; Hartono Hartono; Toto Heru Dwihandoko (Jurnal Manajemen Bisnis Era Digital, 2024)
The purpose of this study is to investigate how interest in Shopeepay is affected by online transactions. Convenience, security, efficiency, promotions, features, and payment variations are the variables in this study. Using a non-probability purposive sampling strategy and incidental sampling methods, questionnaires distributed online via Google Form provided the primary data. Convenience, security, effectiveness, promotions, features, and payment options all have a positive and significant impact on interest in Shopeepay, according to the findings of this study.